The Two Sides of a Single Coin: Karun Rasa and Tragic Feeling - Nagar, Anupam (Miscelánea: A Journal of English and American Studies, 2002)
The paper begins by discussing the Indian idea of Karun Rasa as interpreted by Abhinavgupta, Nagendra, Visvanath, Bhattnayak, Gunchandra, Ramchandra and Raja Bhoja, and then compares it with the Western concept of Tragic Feeling as explained by Aristotle, Hume, Leavis, Schopheneur, Hegel, Nietzsche, Faguet, Butcher, Langer, Dickson, Thorndike, and Murry. Finally it is concluded that the extraordinary opinions of Abhinavgupta, Bhattnayak and Leavis are of outstanding importance in the present context.
Keywords: Karun Rasa; Tragic feeling; Death; Metaphysics; Eastern thought v. Western thought